HYDROCARBON DISTRIBUTION IN SEDIMENTS OF JAKARTA BAY - Agustin Sumartono; Winarti Andayani; Ermin Katrin Winarno (JOURNAL OF COASTAL DEVELOPMENT, 2007)
The analysis of sediments hom stations I, 29, 9, I5, 17 and 25 located in Jakarta Bay were carried out. Sampels were Soxhlet-extracted for I4 hours with methylene chloride J methanol (I: I ), followed by saponi/icatian using KOH in methanol and benzene, Unsaponwcation parts were extracted using n-hexanes. Extracted samples were analyzed using gas chromatography with capiler column of SPB-I. From chromatogram results it was noted that the analysis of sea sediment sea from each station in Jakarta Bay indicate the distribution if n-allranes in the range of CN-C;6 which were dominated by an even carbon. From the results it is assumed that Jakarta Bay sediment may have natural hydrocarbon sources which may come from either the red or blue algae.